A spray containing extracts of oat plantlets and Uncaria tomentosa relieves pain associated with chronic inflammatory skin diseases and dermatological procedures. (1st June 2020) - Reich, A.; Lopez Estebaranz, J.L.; Bahadoran, P.; Guillot, P.; Carballido, F.; Saint Aroman, M.
Abstract: Background: Inflammation from skin conditions such as psoriasis, eczema‐like atopic dermatitis (AD) and hand eczema (HE) and following dermatological procedures (post‐acts) can result in intense itching and cutaneous pain. Dermo‐cosmetics containing plant extracts have been shown to reduce or alleviate these symptoms. Objectives: Assessment of the tolerability and efficacy of a spray containing Rhealba\xAE Oat plantlets and Uncaria tomentosa extracts in adults and children with inflammatory skin diseases and after dermatological procedures. Methods: Data from five open label studies were analysed (Study 1: adults with AD; Study 2: children with AD; Study 3: adults with psoriasis; Study 4: adults with HE; Study 5: adults who had undergone a dermatological procedure: laser, intense pulsed light, glycolic acid peeling, photodynamic therapy or cryotherapy procedure). In all studies, subjects could use the test product up to six times per day for symptom relief. Physical and functional signs of inflammation, treatment‐emergent adverse events (TEAEs), soothing effect, changes in quality of life, cutaneous pain and cosmetic acceptability were compared pre‐ and postapplication. Results: A total of 176 subjects were enrolled across the five studies. Overall, investigators judged the dermatological tolerance of the test product containing Rhealba\xAE Oat plantlets extract and Uncaria tomentosa as good to excellent. All studies showed significant improvements in physical signs, reduction in itching and feeling of pain ( P  < 0.05). The soothing effect was evident after the first application. TEAEs were mostly mild, transient and occurred within the first few days of treatment. The majority of subjects reported improved QoL across the studies. Conclusions: The dermo‐cosmetic spray containing Rhealba\xAE Oat plantlets extract and U. tomentosa was well tolerated and efficacious in providing relief of symptoms associated with cutaneous pain from inflammatory skin diseases and following dermatological procedures; however, further studies are needed to rule out alternative explanations of symptom reduction such as natural history and response biases.